Efficacy and safety of hydrostatic balloon dilatation of ileocolonic Crohn's strictures: a prospective longterm analysis. Issue 4 (April 1995) - Couckuyt, H; Gevers, A M; Coremans, G; Hiele, M; Rutgeerts, P
Abstract : Preliminary reports have suggested that dilatation using hydrostatic through the scope balloons may be useful for the treatment of Crohn's strictures, A prospective longterm follow up (mean (SD) 33.6 (11.2) months) was carried out in 55 Crohn's patients with 59 ileocolonic strictures submitted to 78 dilatation procedures. Hydrostatic balloons were used (Rigiflator, Microvasive) with a diameter of 18 mm on inflation. As soon as the balloons became available dilatation up to a diameter of 20 and 25 mm was attempted. The dilatations were performed under general anaesthesia using propofol (Diprivan). The patients were kept for one night in the hospital after dilatation. Seventy (90%) procedures were technically successful and passage of the stricture with a 13.6 mm diameter colonoscope was possible after 73% of the dilatations. Complications occurred in six patients (11%; 8% of procedures), including sealed perforations (n = 2), retroperitoneal perforations (n = 2), and intraperitoneal perforations (n = 2). Two of the patients were treated surgically with a one stage resection of the stricture and recovered uneventfully. Four patients were treated conservatively with intravenous fluids and antibiotics. There was no mortality. Dilatation completely relieved obstructive symptoms in 20 patients after one procedure, in another 14 patients after two (n = 13) or three (n = 1) dilatations. Total longterm success rate was 34 of 55 patients (62%). Nineteen patients (38%) were operated on because of persistent obstructive symptoms. The data show that endoscopic dilatation using the through the scope hydrostatic balloon system relieves obstructive symptoms resulting from ileocolonic Crohn's strictures. The procedure, however, carries a definite risk of perforation.